2005
DOI: 10.1111/j.0105-1873.2005.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

The European standard series in 9 European countries, 2002/2003 – First results of the European Surveillance System on Contact Allergies

Abstract: Since January 2001, the European Surveillance System on Contact Allergies (ESSCA), supported by European Union funding (contract QLK4-CT-2001-00343), has started to collect patch-test data. This comprises a standardized clinical history and the patch-test results using the European standard series, from 17 centres in 9 European countries listed above. In 2002 and 2003, 10 511 patients' test results have been pooled and analysed. The anamnestic data partly reflect the subspecialties of some centres. The most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
66
4
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 37 publications
8
66
4
6
Order By: Relevance
“…The regularly reported ongoing prevalence study of the NACDG showed steady prevalence rates of 7.8% in 1992-1994 (76), 9.2% in 1994-1996 (73), 9.3% in 1996-1998 (71), 9.2% in 1998-2000 (68) (55)). In most European countries, prevalence rates vary between 2% and 3% (Table 5), and in the recent multicentre European investigations performed by the European Environmental and Contact Dermatitis Research Group (EECDRG) and the European Surveillance System on Contact Allergies (ESSCA), prevalence rates were between 2.0% and 2.3% (59,60,65). These figures, both from the USA and from Europe, thus seem to be reproducible and real.…”
Section: Discussionmentioning
confidence: 81%
“…The regularly reported ongoing prevalence study of the NACDG showed steady prevalence rates of 7.8% in 1992-1994 (76), 9.2% in 1994-1996 (73), 9.3% in 1996-1998 (71), 9.2% in 1998-2000 (68) (55)). In most European countries, prevalence rates vary between 2% and 3% (Table 5), and in the recent multicentre European investigations performed by the European Environmental and Contact Dermatitis Research Group (EECDRG) and the European Surveillance System on Contact Allergies (ESSCA), prevalence rates were between 2.0% and 2.3% (59,60,65). These figures, both from the USA and from Europe, thus seem to be reproducible and real.…”
Section: Discussionmentioning
confidence: 81%
“…6,8,12,[15][16][17][18] Avrupa Kontakt Dermatit Çalışma Grubu (AKDÇG)'nun verilerine göre nikel ile duyarlanma oranı %17,3 ile %24,4 arasında değişmekte olup, en sık genç kadınlarda gözlenmektedir. 13,14,19 Sonuçlarımız literatür bilgileri ile benzerlik göster-mektedir. Ülkemizde kadınlarda nikel ile duyarlanmanın en önemli sebebi küçük yaşlarda kulak deldirilmesi ve nikel içeren imitasyon takı-ların takılması ile açıklanabilir.…”
Section: Discussionunclassified
“…Sonuçlarımız AKDÇG'nin sonuç-ları ile benzer özelliktedir. 13,14,19 Meslek grubu olarak kobalt kloride bağlı duyarlılık sıklıkla polyester reçine ve boyaların imalinde çalışanlarda, metal işçilerinde ve çimento ile mesleği gereği teması olan kişilerde görülmektedir. 21,22 Kadınlar nikel, kobalt ve potasyum dikromat gibi metallerin karışımı ile üretilen metal eşyaların teması sonucu kobalt klorid ile duyarlanmaktadırlar.…”
Section: Discussionunclassified
See 2 more Smart Citations